Herbivore Effects on Ecosystem Process Rates in a Low-Productive System - Maria Tuomi; Sari Stark; Katrine S. Hoset; Maria Väisänen; Lauri Oksanen; Francisco J. A. Murguzur; Hanna Tuomisto; Jonas Dahlgren; Kari Anne Bråthen (Springer New York LLC, 2022)
Mammalian herbivores shape the structure and function of many nutrient-limited or low-productive terrestrial ecosystems through modification of plant communities and plant–soil feedbacks. In the tundra biome, mammalian herbivores may both accelerate and decelerate plant biomass growth, microbial activity and nutrient cycling, that is, ecosystem process rates. Selective foraging and associated declines of palatable species are known to be major drivers of plant–soil feedbacks. However, declines in dominant plants of low palatability often linked with high herbivore densities may also modify ecosystem process rates, yet have received little attention. We present data from an island experiment with a 10-year vole density manipulation, to test the hypothesis that herbivores accelerate process rates by decreasing the relative abundance of poorly palatable plants to palatable ones. We measured plant species abundances and community composition, nitrogen contents of green plant tissues and multiple soil and litter variables under high and low vole density. Corroborating our hypothesis, periodic high vole density increased ecosystem process rates in low-productive tundra. High vole density was associated with both increasing relative abundance of palatable forbs over unpalatable evergreen dwarf shrubs and higher plant N content both at species and at community level. Changes in plant community composition, in turn, explained variation in microbial activity in litter and soil inorganic nutrient availability. We propose a new conceptual model with two distinct vole–plant–soil feedback pathways. Voles may drive local plant–soil feedbacks that either increase or decrease ecosystem process rates, in turn promoting heterogeneity in vegetation and soils across tundra landscapes.